1987
DOI: 10.1007/bf00381275
|View full text |Cite
|
Sign up to set email alerts
|

A petrochemical study of calcic amphiboles from the East Bull Lake anorthosite-gabbro layered complex, District of Algoma, Ontario

Abstract: Mineral Petrol (1986) 93:471-481 request that the following amendments be noted: on page 476, enclenitic should read edenitic; on page 478, Emax should have been omitted in equitation (3) and (4) right hand column.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…[19] Chloride in samples from Yucca Mountain has five main sources: (1) salts or fluids present in fractures; (2) salts or fluids present in intergranular pores; (3) isolated fluid inclusions within mineral grains; (4) chemically bound Cl in hydrous minerals such as biotite and hornblende [Gascoyne, 2003[Gascoyne, , 2002Roback et al, 2002;Kamineni, 1986;Fabryka-Martin et al, 1997, 1998]; and (5) construction water [Finsterle et al, 2002;FabrykaMartin et al, 1997FabrykaMartin et al, , 1998; G. Lu et al, Quantifying water mixing through sample leaching data, submitted to Applied Geochemistry, 2003 (hereinafter referred to as Lu et al, submitted manuscript, 2003)]. The first four sources are common in igneous rocks; the last source (construction water) was introduced during the excavation of the ESF tunnel.…”
Section: Chloride Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Chloride in samples from Yucca Mountain has five main sources: (1) salts or fluids present in fractures; (2) salts or fluids present in intergranular pores; (3) isolated fluid inclusions within mineral grains; (4) chemically bound Cl in hydrous minerals such as biotite and hornblende [Gascoyne, 2003[Gascoyne, , 2002Roback et al, 2002;Kamineni, 1986;Fabryka-Martin et al, 1997, 1998]; and (5) construction water [Finsterle et al, 2002;FabrykaMartin et al, 1997FabrykaMartin et al, , 1998; G. Lu et al, Quantifying water mixing through sample leaching data, submitted to Applied Geochemistry, 2003 (hereinafter referred to as Lu et al, submitted manuscript, 2003)]. The first four sources are common in igneous rocks; the last source (construction water) was introduced during the excavation of the ESF tunnel.…”
Section: Chloride Sourcesmentioning
confidence: 99%
“…The Cl in the rock is higher (about 180 mg/kg) in the TCw and lower (about 120 mg/kg) in the PTn, based on linear interpolation of Cl/Br ratios obtained from step-leaching (repeated grinding and leaching) by FabrykaMartin et al [1998]. We used the rock Cl concentration to represent both fluid inclusions and chemically bound Cl (in hydrous minerals such as biotite and hornblende) [Kamineni, 1986]. However, the maximum Cl leached was found to be only about 10% of the total Cl in the tuff [Gascoyne, 2003].…”
Section: Fluid Inclusion and Mineral Boundary Saltsmentioning
confidence: 99%
“…(For a description of the geology see James & Born 1985;Kamineni 1986). Kamineni et al (1984) identified eight major lithologic units associated with the pluton; anorthosite, gabbroic anorthosite, rhythmically layered gabbro, troctolite, layered gabbro, dendritic gabbro, massive gabbro and fault gabbro. Drillhole EBL-1 intersects all lithologic units, except the fault gabbro.…”
Section: A Diabase Dykementioning
confidence: 99%